PENGARUH PENGHARGAAN EKSTRINSIK, KEMAMPUAN MENYERAP, KERAGAMAN MEDIA DAN HARAPAN MENDAPATKAN TIMBAL BALIK PADA PERILAKU BERBAGAI PENGETAHUAN DAN PEMAHAMAN - SETYOWATI, NUNING (Universitas Sebelas Maret, 2009)
The aim of this study is to examine four of personal factor which predicted influence the person to knowledge sharing. These factor are extrinsic reward, absorptive capacity, channel richness and expectation of reciprocity.